Effectiveness of peritoneal lavage fluid circulating tumour cells and circulating tumour DNA in the prediction of metachronous peritoneal metastasis of gastric cancer (pT4NxM0/pT1-3N+M0) after radical resection: protocol of a prospective single-centre clinical study - Bai, Long; Guan, Yujing; Zhang, Yeqian; Gu, Jiayi; Ni, Bo; Zhang, Hao-yu; Aimaiti, Muerzhate; Wang, Shuchang; Yue, Ben; Xia, Xiang; Zhang, Zizhen (BMJ open, 2024)
BackgroundGastric cancer (GC) is the fourth leading cause of cancer mortality worldwide. Peritoneal metastasis (PM) is a significant cause of death in patients with GC, and presents a major challenge in clinical diagnosis and treatment. Predicting the occurrence of PM in high-risk patients, and diagnosing and treating PM in advance to improve patient survival, remains an unsolved problem in clinical practice. Given the low positive rate of cytology and difficulty in diagnosing occult PM, new molecular markers and detection technologies for early diagnosis require urgent validation. The primary objective of this study is to observe and evaluate the predictive effect of intraoperative peritoneal lavage fluid (PLF) circulating tumour cells (CTC) and circulating tumour DNA (ctDNA) levels in patients with pT4NxM0/pT1-3N+M0 GC on metachronous PM after R0 resection.Methods and analysisThis prospective single-centre clinical study is conducted at Renji Hospital, Shanghai Jiao Tong University School of Medicine. In this study, 200 cases of patients with pT4NxM0/pT1-3N+M0 gastric adenocarcinoma older than 18 years will be screened. Participants will undergo intraoperative PLF CTC and ctDNA testing and will be followed up for 2 years, with imaging assessments performed every 3–6 months until PM occurrs. The primary outcome is the incidence of PM 1 year after surgery, which will be estimated using Clopper-Pearson method, with 95% CIs calculated and compared between groups. Secondary outcome include the incidence of PM 2 years after surgery, overall survival and disease progression. Data will be analysed using the Kaplan-Meier method and the log-rank test.Ethics and communicationInformed consent has been obtained from all subjects. This protocol has been approved by the Ethics Committee of Renji Hospital, Shanghai Jiao Tong University School of Medicine (LY2023-142-B). The findings will be disseminated through peer-reviewed manuscripts, reports and presentations.Trial registration numberChiCTR2300074910.